2018
DOI: 10.1001/jamaoto.2017.3378
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Reported Dysphagia After Thyroidectomy

Abstract: Swallowing symptoms after thyroidectomy are underreported in the literature. This study revealed that as many as 80% of patients who have thyroidectomy may experience swallowing-related symptoms after surgery, and many develop compensatory strategies to manage or reduce the burden of these symptoms. Considering the large number of individuals who may experience subjective dysphagia, preoperative counseling should include education and management of such symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 23 publications
1
29
0
2
Order By: Relevance
“…The manipulation of the perithyroid muscles, as well as intubation and healing, may be the possible causes of vocal and swallowing worsening in the immediate postoperative period [12,13,19,[23][24][25][26]. In the present study, 30.8% of patients (8 patients) had dysphagia in the preoperative period, and 80.8% (21 patients) presented dysphagia in the immediate postoperative period, values close to those found by Krekeler et al (2018) [27], who found dysphagia in 80% of patients (20 cases) after 2 weeks, in 42% (11 patients) at 6 weeks, and in 17% (4 individuals) at 6 months in a qualitative study with 26 patients. These rates were lower than those found by Senise et al (2009) [21], who found an incidence of dysphagia of 87.5% 12 days after thyroidectomy.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The manipulation of the perithyroid muscles, as well as intubation and healing, may be the possible causes of vocal and swallowing worsening in the immediate postoperative period [12,13,19,[23][24][25][26]. In the present study, 30.8% of patients (8 patients) had dysphagia in the preoperative period, and 80.8% (21 patients) presented dysphagia in the immediate postoperative period, values close to those found by Krekeler et al (2018) [27], who found dysphagia in 80% of patients (20 cases) after 2 weeks, in 42% (11 patients) at 6 weeks, and in 17% (4 individuals) at 6 months in a qualitative study with 26 patients. These rates were lower than those found by Senise et al (2009) [21], who found an incidence of dysphagia of 87.5% 12 days after thyroidectomy.…”
Section: Discussionsupporting
confidence: 83%
“…Most studies in this population are still focused on the preservation of vocal function, with few articles on swallowing disorders in the pre-and post-thyroidectomy periods. Furthermore, there is significant variability in the methods employed, especially with regard to the most adequate period for performing the evaluations [8,13,27,28]. It is evident that, regardless of how long after surgery the postoperative evaluation occurs -2 h; 1 day; on the 7th, 12th, or 60th day; 1, 3, or 6 months; or 4 years [6,15,24,27,29,[30][31][32][33][34][35] -the presence of upper airway, vocal and/or swallowing sensory disorders is found, suggesting that this alteration is not directly related to the existence of complications due to intubation, although Peppard and Dickens (1983) [36] and Pereira et al (2003) [24] reported that swallowing function can be altered due to the modification of the sensitivity of the intraoral, pharyngeal, and laryngeal region resulting from intubation.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, most of these surgeries generated unnecessary direct and indirect medical costs, patient anxiety and diminished productivity during recovery, and complications. Although high‐volume thyroid surgeons report relatively low surgical complication rates of 1% to 3%, approximately 26% to 81% of patients undergo surgery with low‐volume surgeons whose complication rates generally are much higher, including hypothyroidism, clinically severe hypocalcemia/hypoparathyroidism, recurrent laryngeal nerve injury, and, less commonly, infection and bleeding . Higher surgical complication rates have been reported among the elderly, who are heavily represented in the thyroid nodule population.…”
Section: Introductionmentioning
confidence: 85%
“…These observations were valuable lessons for us because we expected that our operative approach of using minimal exposure (i.e., lobectomy along with paratracheal lymph node dissection) and neuromonitoring devices in most patients would have a low likelihood of causing any burden to the patients. Investigators from the University of Wisconsin reported that patient-perceived voice changes were frequent (57%) after thyroidectomy, even in the absence of vocal cord paralysis (28), and that 80% of patients had at least one swallowing-related symptom (29). Physicians have underestimated the prevalence of physical symptoms associated with thyroid cancer treatments (30).…”
Section: Discussionmentioning
confidence: 99%